2020
DOI: 10.1177/2325967120903283
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Effects of Remplissage on 6-Month Strength and Range of Motion After Arthroscopic Bankart Repair? A Multicenter Cohort Study

Abstract: Background: Patients who have undergone shoulder instability surgery are often allowed to return to sports, work, and high-level activity based largely on a time-based criterion of 6 months postoperatively. However, some believe that advancing activity after surgery should be dependent on the return of strength and range of motion (ROM). Hypothesis: There will be a significant loss of strength or ROM at 6 months after arthroscopic Bankart repair with remplissage compared with Bankart repair alone. Study Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…32,66 Other management options, such as the Latarjet and other bone block procedures and the remplissage procedure, may have a lower recurrent instability rate but may also lead to complications such as reduced range of motion, altered anatomy complicating revision, nerve injury, and premature osteoarthritis. 18,22,24,36,40,62 This management dilemma has prompted extensive research with the goal of optimizing surgical techniques and refining indications to improve outcomes by matching the appropriate surgical procedure to the appropriate patient.…”
mentioning
confidence: 99%
“…32,66 Other management options, such as the Latarjet and other bone block procedures and the remplissage procedure, may have a lower recurrent instability rate but may also lead to complications such as reduced range of motion, altered anatomy complicating revision, nerve injury, and premature osteoarthritis. 18,22,24,36,40,62 This management dilemma has prompted extensive research with the goal of optimizing surgical techniques and refining indications to improve outcomes by matching the appropriate surgical procedure to the appropriate patient.…”
mentioning
confidence: 99%
“…A common point of contention within the recent literature relates to whether or not adding a remplissage, a nonanatomical procedure, to an arthroscopic Bankart repair results in a clinically important restriction of shoulder range of motion, specifically loss of ER, or patient dissatisfaction in the long term. Clinical, biomechanical, and cadaveric studies have shown that the addition of remplissage may cause loss of ER [44, 52–54]. In addition, in a RCT performed by MacDonald et al [45], the authors reported 10° loss of ER in abduction at 12‐month in patients who had undergone an additional remplissage procedure, yet found no significant difference at 24 months.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 31 , 34 , 35 , 37 The elevated Latarjet procedure complication rates can be attributed to various intraoperative and postoperative factors, namely vascular damage, neurological injuries, and hematoma. 34 Concerning additional clinical benchmarks for remplissage versus Latarjet, literature seems to suggest comparable to marginally higher return-to-sport rates, 7 , 28 reduced internal rotation motion (40.9° vs 53.2°), 35 increased risk of reduced external rotation motion with abduction, 38 , 39 and inconclusive results regarding postoperative pain, with a few studies hinting at neutral to higher marks. 13 , 35 , 39 , 40 Currently, a general lack of long-term follow-up studies regarding said clinical evaluations limit discussion specificity.…”
Section: Discussionmentioning
confidence: 99%